Molecular identification of the fish parasite Lernaea - Pallavi, B.; Shankar, K. M.; Abhiman, P. B.; Ahmed, Iqlas (Indian Journal of Fisheries, 2017)
Isolates of the fish parasitic copepod Lernaea from four different freshwater fishes viz., catla (Catla catla), guppy (Poecilia reticulata), platy (Xiphophorus naculatus) and gold fish (Carassius auratus) were selected for the study. The isolates had considerably differing anchor shapes and were likely to be grouped as different species. Partial nucleotide sequences of the 18S and 28S rDNA regions of the Lernaea isolates were determined. Phylogenetic trees generated by the neighbour joining method revealed that the Lernaea isolates examined in this study were of similar genotype and were identified to be Lernaea cyprinacea.